A Reconfigurable Power Processor for Electric Vehicle Facilitating Both Wired and Wireless Charging - Meher S.R.; Singh R.K. (My University, 2025)
Existing electric vehicles (EV) in the market require two separate power processors for propulsion and on-board wired charging operations. EV with wireless charging feature requires an additional power processing unit to be fitted with the vehicle and thus requires three separate power processors. Existing integrated chargers support any two of these operating modes (i.e., either propulsion and wired charging or wired and wireless charging) out of three required operating modes. In order to optimize size, volume, and weight along with the cost, a novel reconfigurable power processor (RPP) is presented in this article that replaces the need of three separate power processors in an EV. The proposed power processor restructures itself as three different power electronic topologies during three modes of operations. For wireless charging mode, a new converter topology is also proposed in this article for the transmitting unit at the primary side. During both wired and wireless charging methods, the proposed solution draws power from a single-phase ac supply to optimally charge the EV battery pack with CC-CV algorithm and simultaneously maintaining near unity power factor (PF) at the grid side. The proposed idea is validated in the laboratory environment with an experimental set up consisting of a 24 V, 400 W BLDC motor and a 24 V, 30 Ah battery. © 2014 IEEE.